Impact of Sports Psychology, Human Behavior, and Advertisement on the sales of player’s shirts and drinks - Ruilin Xu; Priyanut Wutti Chupradit; Supat Chupradit; Worakamol Wisetsri; Abdelmohsen A. Nassani; Mohamed Haffar; Wanich Suksatan, M.Sc., RN (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Growing health concerns and being overweight as a result of excessive consumption of soft drink have become a major concern around the world. The primary purpose of this research study is to measure the effect of sports psychology, human behavior, and advertisement on the sale of player's shirts and drinks. This research study uses primary data analysis, collected through a questionnaire including specific questions related to the independent and dependent variables understudy. In this research study, sports psychology, human behavior, and advertisement are consider independent variables, and sales of player's shirts and sales of drinks are the dependent variables. For measuring data analysis, the study uses chi-square analysis, descriptive statistical analysis, regression analysis, least-square analysis and other histogram graphs. According to the overall study results, it has been found that sport psychology shows a positive and insignificant impact on the sale of players' shirts. On the other hand, human behavior is found to have a negative but significant impact on the sale of players' shirts. In other words, sport psychology has a negative effect on the sale of drinks, and human behavior has a positive effect on drinks sales. This study has important implications for marketers and policy-makers concerned with public health in general, and obesity reduction in particular. Through social marketing, soft drink marketers may incorporate obesity-reduction activities. This study proposes a conceptual framework soft drink anti-consumption behavior, emphasizing health concerns and exploring the impact of sociocultural variables on anti-consumption.